2011
DOI: 10.1111/j.1464-5491.2010.03180.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mobile phone intervention for diabetes on glycaemic control: a meta-analysis

Abstract: Results pooled from the included trials provided strong evidence that mobile phone intervention led to statistically significant improvement in glycaemic control and self-management in diabetes care, especially for Type 2 diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
416
7
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(462 citation statements)
references
References 45 publications
24
416
7
15
Order By: Relevance
“…Piette et al kontrol grubuna göre 12 ay telefonla takip edilen ve sesli mesajla izlenen 124 diyabetli bireyin AKŞ düzeylerinin anlamlı ölçüde azaldığını (41 mg/dl) bildirmişlerdir (28). Kim & Jeong telefonla takip ettikleri ve sesli mesajla 3 ay izledikleri diyabetli bireylerin kontrol grubuna göre AKŞ ve TKŞ düzeylerinde azalma olmakla birlikte, aralarında istatistiksel olarak anlamlı bir fark olmadığını Tab lo 3: Araştırma gruplarına göre ÇBDÖ'nin alt boyutlarının önceki ve 12 hafta sonraki puanlarının dağılımı (n=120) (12,13,27,28,32,33,34,35,36,37), bulgumuz önceki çalışma sonuçlarını doğrulamaktadır. Bununla birlikte NICHE çalışmasında 12 haftalık izlem sonunda gruplar arasında HbA1c düzeylerin-de anlamlı bir fark olmadığını bildirilmiştir (38).…”
Section: Discussionunclassified
“…Piette et al kontrol grubuna göre 12 ay telefonla takip edilen ve sesli mesajla izlenen 124 diyabetli bireyin AKŞ düzeylerinin anlamlı ölçüde azaldığını (41 mg/dl) bildirmişlerdir (28). Kim & Jeong telefonla takip ettikleri ve sesli mesajla 3 ay izledikleri diyabetli bireylerin kontrol grubuna göre AKŞ ve TKŞ düzeylerinde azalma olmakla birlikte, aralarında istatistiksel olarak anlamlı bir fark olmadığını Tab lo 3: Araştırma gruplarına göre ÇBDÖ'nin alt boyutlarının önceki ve 12 hafta sonraki puanlarının dağılımı (n=120) (12,13,27,28,32,33,34,35,36,37), bulgumuz önceki çalışma sonuçlarını doğrulamaktadır. Bununla birlikte NICHE çalışmasında 12 haftalık izlem sonunda gruplar arasında HbA1c düzeylerin-de anlamlı bir fark olmadığını bildirilmiştir (38).…”
Section: Discussionunclassified
“…A recent review focused on the effect of mobile phone interventions for diabetes on glycemic control (29) and carried out a meta-analysis of 22 trials with 1,657 participants. This showed that mobile phone interventions for diabetes self-management reduced HbA 1c values by a mean of 6 mmol/mol or 0.5% (95% CI 0.3 to 0.7) over a median follow-up duration of 6 months.…”
Section: The Impact Of Mobile Phone Interventionsmentioning
confidence: 99%
“…However, there is a paucity of similar data in patients with type 2 diabetes. Previous systematic reviews of telecare intervention in type 2 diabetes have assessed the usage of web-based systems (5,6) or mobile phones (7,8) separately to monitor diabetes care. Some of the reviews have considered telecare intervention contents, technologies, and frequencies, but they did not consider adequately the usage of combination technologies in practice, the nature of feedback receipt in telecare, the ethnic differences, etc.…”
Section: Introductionmentioning
confidence: 99%